2022
DOI: 10.1109/tits.2021.3087158
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking and Designing a High-Performing Automatic License Plate Recognition Approach

Abstract: In this paper, we propose a real-time and accurate automatic license plate recognition (ALPR) approach. Our study illustrates the outstanding design of ALPR with four insights:(1) the resampling-based cascaded framework is beneficial to both speed and accuracy; (2) the highly efficient license plate recognition should abundant additional character segmentation and recurrent neural network (RNN), but adopt a plain convolutional neural network (CNN); (3) in the case of CNN, taking advantage of vertex information… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 42 publications
(93 reference statements)
0
11
0
Order By: Relevance
“…The license plate number in the video can be processed at a speed of 9 frames per second. Wang et al [10] proposed a novel two-stage detection method. Their proposed method uses VertexNet and SCR-Net to combine, their detection uses VertexNet method, and their recognition uses SCR-Net.…”
Section: Related Workmentioning
confidence: 99%
“…The license plate number in the video can be processed at a speed of 9 frames per second. Wang et al [10] proposed a novel two-stage detection method. Their proposed method uses VertexNet and SCR-Net to combine, their detection uses VertexNet method, and their recognition uses SCR-Net.…”
Section: Related Workmentioning
confidence: 99%
“…Wang et al [3] propose a two-step process for license plate detection and recognition by designing two specialized networks. For detection, VertexNet is designed to extract the spatial information of the license plate and later on uses this information to rectify the detected license plate image.…”
Section: B License Plate Detection and Recognitionmentioning
confidence: 99%
“…Leveraging upon the installed surveillance cameras of toll plazas, we propose an image-based solution for toll tax collection. Such a solution is motivated by the recent state-ofthe-art results achieved by the usage of convolution neural network (CNN) for image-based vehicle type [2] and license plate recognition [3]. Our framework calculates the toll tax of a vehicle from its image using three steps strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [16] was presenteda weight-sharing classifier that can detect all occurrences of a character in any place. Small cross-dataset studies have been conducted in recent years to test the generalizability of the suggested approaches, since recognition rates using the classic split methodology have grown dramatically in recent years.…”
Section: Introductionmentioning
confidence: 99%